Design of a monitoring network as a participative management tool: physical and chemical quality of groundwater in three sub-basins in the Central Valley of Costa Rica - Madrigal-Solís, Helga (2019)
The groundwater of the Barva, Upper Colima, and Lower Colima aquifers, located in the western part of the Central Valley of Costa Rica represents the main source of drinking water in this region. The purpose of this study was to design a monitoring network to evaluate groundwater quality in these aquifers within the sub-basins of the Bermúdez, Ciruelas and Río Segundo rivers, and to encourage the participation of stakeholders. Five proposed sites exceeded, in between two and four occasions, the Alert Value of 25 mg/l nitrate as NO3-. These sites, which capture water from the Barva aquifer, were located in areas where urban use and coffee crops predominated. The sites that collected water from this aquifer with the lowest concentrations, below 2 mg/l, were found in the upper sub-basins, where forest and pastures predominate, while those that collected water from the Colima aquifers showed concentrations below 20 mg/l. At least semi-annual monitoring of electrical conductivity, pH, temperature, nitrates and chlorides is recommended. The operation of these networks provides an opportunity for monitoring groundwater quality by stakeholders at basin level as one of the first steps in developing sustainable management of this resource.